POLA ASUH KELUARGA TERHADAP PRESTASI BELAJAR ANAK - Syahril Chaniago (Jurnal Ilmiah Econosains, 2014)
AbstractParental factors determine the establishment of children’s intelligence in the process of maintaining, actualizing and giving meaning to their spiritual life. In the process of socialization of the children, there are various parties that may play roles. These parties can be categorized as a certain social group and particular individual. Discussing the issue of education and children development is something endless. At the present time we can see there are many advanced steps that have been recorded from the research and discovery about new theories of education. This brings great hope for the development of the teaching or education system, as well as making a significant contribution in improving the learning process in education that has been trapped by a narrow pragmatism system. In addition, the output of the school is also oftencontributing to a disorientation of personality.